Contemporary practices of Portuguese and Brazilian soccer coaches in designing and applying small-sided games - Clemente, Filipe; Afonso, José; Silva, Rui Miguel; Aquino, Rodrigo; Vieira, Luiz Palucci; Santos, Fernando; Teoldo, Israel; Oliveira, Rafael; Praça, Gibson; Sarmento, Hugo (Biology of Sport, 2024)
This descriptive study aimed to investigate the current practices of Portuguese and Brazilian soccer coaches in the design and implementation of small-sided games (SSGs) in soccer. A total of 187 male coaches participated in the online survey, consisting of 82 Portuguese and 105 Brazilian individuals. These coaches held various positions within the technical staff, with 63 serving as head coaches, 38 as assistant coaches, 38 as physical trainers, and 48 in other roles related to the technical staff. Additionally, the participants represented both youth ( n = 102) and adult competitive levels ( n = 59), along with some who were not currently associated with a specific group. The survey consisted of 32 questions divided into three main sections: (i) the timing of SSG application, (ii) the methods used for applying SSGs, and (iii) the reasons for applying SSGs. The Chi-square test revealed a statistically significant association between nationality and the frequency of SSGs used in training sessions during the pre-season ( p = 0.039) and in-season ( p < 0.001). Moreover, significant association between nationality and the time allocated to employing SSGs for targeting aerobic training ( p < 0.001) was found. There was a significant association between nationality and the weekly frequency of SSGs use for targeting sprint training ( p = 0.019). The Chi-square test identified significant associations between nationality and the use of SSGs for targeting technical training ( p = 0.002), as well as for tactical training ( p = 0.002). In summary, this study underscores that SSGs are primarily employed to enhance aerobic fitness, change of direction, technical skills, and tactical behaviors. Coaches generally favor employing SSGs two to three times a week, with typical sessions lasting between 16 to 30 minutes. Notably, the major discrepancies between nationalities lie in the importance assigned to the use of SSGs. However, in practice, the formats and objectives for implementing SSGs remain relatively similar